Неонатална сепса – Клиничко-етиолошки профил у центру за терцијарну негу у Јужној Индији: сепса - Kamalakannan, Santosh Kumar (Halo 194 - naučni časopis urgentne medicine, 2022)
Abstract : Introduction : Neonatal sepsis is a leading cause of mortality and morbidity among the neonates.Neonates are at risk of sepsis due to several immaturities that they possess inherently. Sepsis is classified as early onset or late onset and the pathogenesis is different for both of them .This study was done to determine the microbial pattern and clinical presentation of neonates admitted with suspicion of sepsis, in GovtKilpauk Medical College Hospital, a tertiary care center. Methodology: Study method: Descriptive Cross Sectional Study. Study place: Govt.Kilpauk medical college Hospital Results : Of the 207 neonates admitted with suspected sepsis 112 were males and 97 were female .11 babies were of very low birth weight, 107 newborns were of low birth weight, 88 babies were in normal birth weight and one baby weighed more than 4,000 grams. Blood culture was positive in 88 out of the 207 cases(42.51%). Klebsiella is the commonest organism causing sepsis(45%) in our Neonatal Intensive Care Unit. Other isolates included EscherichiaColi (31%), Pseudomonas (6%), Enterobacter (1%) and Acinetobacter (2%). The Gram positive organisms were Coagulase Positive and Coagulase negative Staphylococci(8%), Group B Beta Hemolytic Streptococcus (5%) and Enterococcus (2%).Overall sensitivity among Gram-negative isolates was to Imipinem (92%) followed by Amikacin (82.66%) and best sensitivity among Gram positive isolates was to Vancomycin(84.61%), followed by Cloxacillin and Ampicillin ( 61.53%).Out of 88 positive cultures 6 were multi-drug resistant(6.8%). Conclusion: Knowledge about the microorganism causing sepsis in neonates helps in preventing morbidity, mortality and emergence of antibiotic resistance.